Assessing the Impact of Think-Pair-Share on Learning Comparative Degree in 8th Grade Students - Viriana (English Language and Literature in Education Journal, 2024)
This study investigates the impact of the Think-Pair-Share (TPS) technique on the understanding of comparative degrees among the 42 eighth-grade students at SMP Negeri 48 Surabaya. Using a quasi-experimental design with a pretest-posttest control group, the research compared the effectiveness of TPS against traditional teacher-based teaching methods. The participants were divided into two groups: the experimental group received instruction through the TPS technique, while the control group was taught using conventional methods. The study measured the students’ grasp of comparative degrees through pretests and posttests, assessing improvements in academic performance and comprehension. Analysis of the data revealed that the experimental group, which utilized the TPS method, achieved significantly higher posttest scores compared to the control group. This result underscores the effectiveness of the TPS technique in enhancing the students’ understanding and retention of grammatical concepts. The findings advocate for the integration of TPS into instructional practices, as it facilitates active learning and improves educational outcomes. The research suggests that TPS not only engages students more effectively but also leads to better academic performance in learning comparative degrees. Consequently, the study supports the broader application of TPS in English grammar education to foster active learning environments and improve student achievements in junior high school settings.